Synthesis and Optimization of Deesterified Acacia-Alginate Nanohydrogel for Amethopterin Delivery. (11th February 2022) - Sathish, T.; Sabarirajan, N.; Prasad Jones Christydass, S.; Sivananthan, S.; Kamalakannan, R.; Vijayan, V.; Paramasivam, Prabhu
Abstract : Naturally obtained materials are preferable for the production of biomedicine in biomedical applications. Acacia gum is has recently become a hopeful one in the biomedicine production due to its excellent properties, namely, emulsifier, stabilizing mediator, suspending agent, etc. In this novel work, we synthesised and characterized the deesterified Acacia gum-alginate nanohydrogel (DEA-AG NPs) as a carrier for amethopterin (ATN) delivery. This combination is used in the drug effectiveness and tissue engineering. In this work, the Taguchi route is implemented for estimating of particle size and zeta potential (mV) through optimization. Following three parameters are considered for this work: DEA solution concentration (0.008, 0.016, 0.024, and 0.032 w/v %), alginate molecular weight (3, 6, 9, and 12 MW), and ATN/DEA ratio (1 : 4, 1 : 8, 1 : 12, and 1 : 16 w/w %). In particle size analysis and zeta potential analysis, the DEA solution concentration is highly influenced. Minimum particle size is found as 148.50 nm. Similarly, maximum zeta potential is identified as 29.5 mV.